Conceptualizing Sustained High Quality Fashion Products in a Devalue Dominated Marketplace. (4th May 2017) - Cassidy, Tracy Diane
Abstract: The current fashion system largely sustains an industry through excessive consumer consumption habits resulting in an environmentally unsustainable industry. Fashion trends coupled with mass-production strategies, predominantly within the lower and middle market sectors, is considered by many to have devalued fashion; and has impacted on the higher end of the market, forcing brands to reconsider their quality and price points to remain profitable, or to tolerate lower sales volumes. The online auction culture is a further consideration, with consumers having ready access to cheaper luxury goods, albeit second-hand, which supports the continuing growth of vintage and retro trends reinforced by trend forecasters and endorsed by those with an interest in a more sustainable lifestyle. This presents high-end brands with an opportunity to strengthen their position in a changing marketplace. This paper deliberates factors that contribute to the devaluing of quality before debating the opportunity that the new online culture presents to the high-end sector with the inclusion of a conceptual business model. While conceptual, after deliberating notions from fashion history and from current affairs, the paper proposes an optimistic future for luxury fashion brands and products if new technologies, such as online tools and facilities, and advancing consumer behavior preferences are embraced and utilized to full capacity. It is not to be suggested, however, that the conceptual business model is solely for the purpose of the online retail context.